Business Saving and Normal Income - Lancaster, Tony (Review of Economic Studies, 1963)
Journal Article Business Saving and Normal Income Get access Tony Lancaster Tony Lancaster Cambridge Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 30, Issue 3, October 1963, Pages 203–216, https://doi.org/10.2307/2296321 Published: 01 October 1963